Anxiety among cancer patients: A cross-sectional study at The University of Gondar comprehensive specialized hospital - Hailu Aragie; Dagnew Getnet Adugna; Nega Dagnew Baye; Habtu Kifle Negash (PLoS ONE, 2025)
Introduction Anxiety is a prevalent psychological issue among cancer patients, significantly affecting their quality of life and potentially influencing treatment outcomes. This study aims to investigate the prevalence and associated factors of anxiety among cancer patients at the University of Gondar Comprehensive Specialized Hospital in Northwest Ethiopia. Methods A cross-sectional study design was used, involving 384 cancer patients, selected by systematic random sampling technique, from the oncology ward. Data were collected using the Generalized Anxiety Disorder 7-item (GAD-7) scale and the Oslo Social Support Scale (OSS-3). Descriptive and inferential statistics, including bi-variable and multi-variable logistic regression analyses, were employed to analyze the data. Results The prevalence of anxiety was 88.3%, with 34.4% of patients experiencing severe anxiety, 29.2% moderate anxiety, and 24.7% mild anxiety. Significant predictors of anxiety included participants age>= 61years (AOR =  2.99, 95% CI =  1.31–6.79), participants age 30-60 years (AOR =  4.13, 95% CI =  1.53–11.07), female sex (AOR =  2.04, 95% CI =  1.02–4.07), advanced cancer stage (AOR =  3.08, 95% CI =  1.11–8.53), and ongoing treatment (AOR =  2.40, 95% CI =  1.14–5.10). Conclusion The study found a high prevalence of anxiety among cancer patients, compared to the previous studies, highlighting the need for integrated psycho-oncology services. Specific interventions are necessary for high-risk groups, including older patients, females, and those with advanced-stage cancer.